TAKSONOMI TUMBUHAN OBAT DI DESA RIANG BANDUNG KECAMATAN MADANG SUKU DUA OKU TIMUR (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
Research of taxonomy of fitopharmaca species was conducted at Riang Bandung  village in Madang Suku Dua Recency, Sumatera Selatan Province  on June till July 2013. The objective of this research was Plant had fitopharmaca potency. This research utilited the direct  observation with    around research location  during two weeks.  The result of the research gated 1 division, 2 class,  10  order,  10 family, 13 genera and 14 species as Imperata cylindrica , Curcuma domestica, Zingiber officinale, Alpinia galanga, Carica papaya, Citrus aurandifolia, Cinnamonum zeylanicum, Annona muricata, Piper betle, Piper nigrum, Jatropa curcas L. , Manihot utilisma,  Psidium guajava L., dan  Justicia gandarussa. Key words: taxonomy, fitopharmaca